(Auto)biographical research perspectives for musical education: a metanarrative exercise (Orfeu, 2022)
This essay article has the goal to reflect about the (auto)biographical research perspective crossed by studies I have been making through a metanarrative exercise over the last years. In this endeavor, I make antithesis among (auto)biographical productions, their theoretical-methodological foundations and recent epistemological ponderings enabled by Xxxxx. Specifically, I go through some foundations on the training research and educational biography, as well as concepts arising from the researches made on these cores and from recent readings that in addition to update the comprehension about the development and scientific research, it substantiates in a powerful epistemological field so we can also think of music as its own senses. Thereby, I crave on advancing in the comprehension about the music place in the research on (auto)biographical and the potency of this last one so that we can think of the human development with and through the music.
Keywords: musical-educational biography; training research